Ablation of the prion protein (PrP) gene in mice prevents scrapie and facilitates production of anti-PrP antibodies. - Prusiner, S B (1993)
Mice, homozygous for prion protein (PrP) gene ablation (Prn-p0/0), develop normally and remain well > 500 days after inoculation with murine scrapie prions. In contrast, wild-type mice developed scrapie < 165 days after inoculation and most Prn-p0/+ mice, heterozygous for disruption of the PrP gene, exhibited signs of central nervous system dysfunction between 400 and 465 days after inoculation. In situ immunoblots showed widespread deposition of scrapie PrP (PrPSc) in the brains of both wild-type Prn-p+/+ and Prn-p0/+ mice, while neither cellular PrP (PrPC) nor PrPSc was detected in the brains of Prn-p0/0 mice. In contrast to Prn-p+/+ and Prn-p0/+ mice, Prn-p0/0 mice failed to propagate prion infectivity as measured by bioassays. Syrian hamster (SHa) PrP transgenes rendered Prn-p0/0 mice susceptible to prions containing SHaPrPSc. Immunization of Prn-p0/0 mice with purified, infectious mouse or SHa prions dispersed in Freund's adjuvant produced antisera that bound mouse, SHa, and human PrP on Western blots. Presumably, the lack of PrPC expression in Prn-p0/0 mice prevents them from becoming tolerant to the immunogen. The resistance of Prn-p0/0 mice to developing scrapie after inoculation with murine prions supports the hypothesis that PrPSc is essential for both transmission and pathogenesis of the prion diseases.